PERAN PELATIHAN KEWIRAUSAHAAN TERHADAP PEMBANGUNAN EKONOMI DESA LERANG DI MASA PANDEMI - Arwadi, Fajar; Mujahidah, Nurul; Hulaifah, Andi Annisa; Wahyuni, Sri; Abd. Wafi, Muh Isnain; Haris, Hasnawi; Suarlin, Suarlin (Jurnal Pengabdian Masyarakat Berkarya, 2023)
The covid-19 pandemic caused Indonesia's economic conditions to experience chaos. No exception in Lerang Village, Lanrisang Subdistrict, Pinrang Regency where many shops or businesses owned by residents suffered losses. The observations showed that the majority of residents in Desa Lerang cultivated fish to be one of the sources of food anpd income in the pandemic. From the observation, fish cultivated after harvesting will be directly sold to the market or consumed directly without trying to process it first into a higher value product. After further observation, the team of Thematic Community Service (KKNT) from Universitas Negeri Makassar (UNM) found that the fish cultivated by the community was suitable for processing into “Abon Ikan”, then the KKNT UNM Team began to prepare the things needed to socialize it. This socialization is coupled in the entrepreneurship training conducted on August 26, 2021 in which there are three materials, namely: “Abon Ikan” making, personal branding, and entrepreneurship management. This activity increases people's understanding of the importance of entrepreneurship in this pandemic period, which can be seen from the enthusiasm of citizens in participating in this activity. As an exterior of this activity, the KKNT UNM Team formed a business unit consisting of lerang villagers and was shadowed directly by BUMDes. Therefore, this business unit came as one of the solutions in overcoming the economic problems faced by the people of Lerang Village during the covid-19 pandemic.